FACTORS AFFECTING LAND USE CHANGE AND ITS IMPACTS IN THE EASTERN HILLS OF NEPAL - Puspa SHARMA; Pushkar K. PRADHAN (Studia Universitatis Babeş-Bolyai: Geographia, 2016)
Factors Affecting Land Use Change and Its Impacts in the Eastern Hills of Nepal. The objective of this paper is to explore factors causing change in land use and land cover categories in the Eastern Hills of Nepal’s during the past 24 years between 1986 and 2010. The paper draws data and information from three different map sources —land resource mapping project 1986, toposheet 1996 and Landsat imagery 2010. In addition, the mapping data being generated were verified in the field through using observation, reality check approach and consultation workshops held at different places in the Eastern Hills of Nepal. The study area comprises four contagious hill districts such as Bhojpur, Dhankuta, Sankhuwasabha, and Terhathum.